The effect of stress on paleomagnetic signals: a micromagnetic study of magnetite's single-vortex response - North,T; Muxworthy,A; Williams,W; Mitchell,T; Collins,G; Davison,T (Geophysical Research Letters, 2024)
In this study we use micromagnetic modeling to show that the magnetizations of magnetically single-vortex particles rotate toward the stress axis on the application of a differential compression stress. This is the exact opposite response to magnetically single-domain particles, which previously provided the theoretical underpinning of the effect of stress on the magnetic signals of rocks. We show that the magnetization directions of single-vortex and equant single-domain particles are altered by much lower stresses than previously predicted, c.f., 100 versus 1,000 MPa; where a change in magnetization is defined as a rotation of >3° after the removal of stress. The magnetization intensity of assemblages also drops by ∼20%–30% on the application and removal of stress of ∼100 MPa. Given that single-vortex particles are now thought to dominate the magnetization of most rocks, future studies should account for paleomagnetic directional uncertainties and potential underestimation of the ancient magnetic field intensity.